Lossless Snubber-Based Bidirectional Full-Bridge Converter for Renewable Energy Applications - Qusay Jabbar Harjan; Noora Salim (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
In this study, we offer a new isolated bidirectional converter., which utilizes a novel snubber to provide soft switching for both primary switches without introducing additional energy losses to the snubber circuitry. The suggested converter has a low number of components and its control is simplified due to the fact that only one switch operates on each side. The performance of the proposed converter has been thoroughly analyzed and validated through simulation using PSPICE software, confirming the theoretical analysis of the converter.